Answer:
(0,4)
(2,2)
Step-by-step explanation:
y=x^2-3x+4
x+y=4
the second one can be rewritten as y=4-x
so the system becomes
y=x^2-3x+4
y=4-x
therefore 4-x = x^2-3x+4
that is x^2-2x=0
we can write it as x(x-2)=0 a product is = 0 when one of its factors = 0
so the solutions for x are: x=0 and x-2= 0 that means x=2
to get y you simply use 0 and 2 as value of x for any of the two equations
and you get y=4 and y=2 respectively
Answer:
c
Step-by-step explanation:
Answer:
5
Step-by-step explanation:
The square Root of 25 in its simplest form means to get the number 25 inside the radical √ as low as possible.
25 is a perfect square, which means that you can simply calculate the square Root of 25 to get the answer. 5 times 5 equals 25. Thus, the square Root of 25 in simplest radical form is:
5